Subantarctic mode water in the southeast Pacific: effect of exchange across the Subantarctic Front - Holte, JW; Talley, LD; Chereskin, TK; Bernadette Sloyan (2013)
This study considered cross-frontal exchange as a possible mechanism for the observed along-front freshening and cooling between the 27.0 and 27.3 kg m − 3 isopycnals north of the Subantarctic Front (SAF) in the southeast Pacific Ocean. This isopycnal range, which includes the densest Subantarctic Mode Water (SAMW) formed in this region, is mostly below the mixed layer, and so experiences little direct air-sea forcing. Data from two cruises in the southeast Pacific were examined for evidence of cross-frontal exchange; numerous eddies and intrusions containing Polar Frontal Zone (PFZ) water were observed north of the SAF, as well as a fresh surface layer during the summer cruise that was likely due to Ekman transport. These features penetrated north of the SAF, even though the potential vorticity structure of the SAF should have acted as a barrier to exchange. An optimum multiparameter (OMP) analysis incorporating a range of observed properties was used to estimate the cumulative cross-frontal exchange. The OMP analysis revealed an along-front increase in PFZ water fractional content in the region north of the SAF between the 27.1 and 27.3 kg m − 3 isopycnals; the increase was approximately 0.13 for every 15° of longitude. Between the 27.0 and 27.1 kg m − 3 isopycnals, the increase was approximately 0.15 for every 15° of longitude. A simple bulk calculation revealed that this magnitude of cross-frontal exchange could have caused the downstream evolution of SAMW temperature and salinity properties observed by Argo profiling floats.